The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1007/s11095-009-0006-0
|View full text |Cite
|
Sign up to set email alerts
|

Local Delivery of Ferrociphenol Lipid Nanocapsules Followed by External Radiotherapy as a Synergistic Treatment Against Intracranial 9L Glioma Xenograft

Abstract: The synergistic effect between ferrociphenol-loaded LNCs and radiotherapy was due to a closely oxidative relationship. Upon these considerations, Fc-diOH-LNCs appear to be an efficient radiosensitive anticancer drug delivery system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 36 publications
2
45
0
Order By: Relevance
“…Another study confirms the reproducibility of the model as we obtained the same improvement in survival in the radiation group compared to the untreated group [18]. Therefore, this radiation therapy protocol has the potential to induce strong tumor debulking and facilitate concomitant chemotherapy treatment.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Another study confirms the reproducibility of the model as we obtained the same improvement in survival in the radiation group compared to the untreated group [18]. Therefore, this radiation therapy protocol has the potential to induce strong tumor debulking and facilitate concomitant chemotherapy treatment.…”
Section: Discussionsupporting
confidence: 75%
“…In his study, he tested a single high dose of radiation (ranging from 20 to 45 Gy) with radiosurgery in a limited volume. Previously, we investigated a radiation therapy schema in 3 fractionated doses of 6 Gy a week in vitro on 9L cell lines without and with concomitant chemotherapy [18]. The results showed that cell death was most important as the number of fractions increased from 1 to 3 and the increase was higher for the schemas associated with chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…With our therapeutic tool based on the use of MIAMI cells, an increase in survival was obtained with a dose of Fc-diOH of about 3.6 µg/animal, as opposed to the 360 µg/animal reported for the convection-enhanced delivery of Fc-diOH-LNCs. 29,39 This drug delivery system is therefore very promising for improving the local tissue distribution of drugs in GBs and for limiting side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been reported that local irradiation may enhance the migration and engraftment specificity of MSCs, 42 in addition to potentiating the cytotoxic action of Fc-diOH. 39 …”
Section: Discussionmentioning
confidence: 99%
“…The activity of the Fc-diOH-LNCs was evaluated in 9L cells in association with radiotherapy (RT) and a combined treatment using the CED of Fc-diOH-LNCs with external beam RT was evaluated in 9L glioma-bearing rats (35). For the combined RT, sucrose was dissolved in the aqueous phase of the LNC suspension after formulation, to enhance the viscosity of the infusion, and its presence did not affect the LNC size and had no toxic effect on cells in vitro .…”
Section: Lipid Nanocapsulesmentioning
confidence: 99%